The Law Enforcement against Alcoholic Drinks Habits - Leni Dwi Nurmala; Robby Waluyo Amu; Dince Aisa Kodai; Nurwita Ismail; Yusrianto Kadir (Jurnal Daulat Hukum, 2022)
The problem of alcohol abuse in various circles, both in society and among teenagers, has become a problem that continues to experience a very significant increase and tends to increase every year. When teenagers or people have the habit of consuming liquor, it can lead to crime, in various forms that vary greatly, for example juvenile delinquency, fights, the emergence of juvenile gangs, thuggery, immoral acts and others. Juridically there is no prohibition of liquor or alcoholic beverages, but only on the regulation of procurement, distribution, sale and control. The existing laws and regulations in Indonesia have not been able to fully accommodate to be able to control the circulation of alcoholic beverages because some of the regulations that have been spread have not been specifically and comprehensively able to suppress the circulation and even prevent alcoholic beverages in the community. As a result, regulations at the lowest level (regional regulations) can only carry out prevention locally at the provincial level which has regional regulations concerning the Control and Supervision of alcoholic beverages, such as Gorontalo Provincial Regulation No. 16 of 2015. The Gorontalo Provincial Government considers it very important that the control and supervision of the circulation of alcoholic beverages must be carried out in order to prevent disturbances to peace, order and public security.